The oxidation of elemental sulphur by Thiobacillus denitrificans - M. Aminuddin, (Universiti Pertanian Malaysia, 1979)
The oxidation of elemental sulphur in Thiobacillus. denitrificans is catalysed by an enzyme present in the S114 fraction;GSH and a heat-stable factor are requIred for the reaction. Sulphur oxidation may be linked to oxygen uptake in the S144 fraction and to nitrate reduction in the crude extract (310). The initial product of sulphur oxidation is sulphite.